Efectos de la aplicación de insecticidas de última generación en el control del Gusano cogollero (Spodoptera frugiperda Smith) en el cultivo del maíz (Zea mays L.) - Franco Veliz, Brian Alexi (2019)
This experimental work was carried out on the grounds of Mrs. Aura Moran Mindiola, located in the “La Veliz” farm, inside the Hda. “La Muralla”, at the San Rafael entrance, passing El Lechugal, via Panamericana. The area belongs to the jurisdiction of the Mocache canton, Los Ríos Province. The geographical coordinates are 357221.6 UTM south latitude and 143725.5 UTM west longitude and 12 meters above sea level. The soil has a flat topography, clay loam texture and regular drainage. As a planting material, the Emblema corn hybrid was used. The treatments studied were Lufenuron + Emamectin Benzoate in doses of 400 g + 100 g; Chlorantraniliprole + Thiamethoxam dose of 200 g + 200 g; Chlorfenapyr + Methoxyfenoside dose of 160 g + 80 g; Indoxacarb dose of 150 g; Amamectin benzoate dose of 50 g and Cypermethrin (absolute control) dose of 250 cc. In this research work the experimental design of Random Complete Blocks with 6 treatments and 4 repetitions was used. To perform the treatment evaluation, the 95% probability Tukey test was used. Based on the results obtained, it was determined that the masses of eggs and larvae did not influence corn cultivation, since there were no significant differences in the evaluations carried out. The ranges ranged from 0.0 to 1.3 masses; regarding the percentage of plants attacked in the different evaluations no statistical significance was detected in the evaluations from 7 to 42 days after planting and the values fluctuated between 0.0 and 17.5%; the variables diameter and length of ear, grains per ear, weight of 1000 grains and yield obtained the highest average with treatment that Amamectin Benzoate was applied in a dose of 50 g.